1977
DOI: 10.1093/infdis/136.5.609
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Bordetella pertussis Phase I to Mucociliary Clearance by Rabbit Tracheal Mucous Membrane

Abstract: Cultivated mucous membrane of rabbit trachea was point inoculated with Bordetella pertussis phase I or III. Phase I (virulent) bacteria were found to be infective at the point-inoculated site, but phase III (avirulent) bacteria rarely showed such behavior. After inoculation, homogenized segments of mucous membrane were spread on plates. Large numbers of phase I bacteria were recovered from the inoculated segment; however, the laryngeal segment was the site of recovery of large numbers of phase III bacteria. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…
PLATES VIII-XIIN previous studies Bordetella pertussis was shown to be resistant to the mucociliary clearance mechanism of the rabbit trachea (Matsuyama, 1977). Scanning electron microscopy readily demonstrated B.pertussis organisms associated with clusters of the cilia of the epithelial cells.
…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…
PLATES VIII-XIIN previous studies Bordetella pertussis was shown to be resistant to the mucociliary clearance mechanism of the rabbit trachea (Matsuyama, 1977). Scanning electron microscopy readily demonstrated B.pertussis organisms associated with clusters of the cilia of the epithelial cells.
…”
mentioning
confidence: 79%
“…Each explant was washed with 2 ml of saline, expelled through a 22-gauge needle at the rate of 0.6-0.8 ml/s to free the ciliated surfaces from mucus. Fixation and observation were as described previously (Matsuyama, 1977).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of B. pertussis to adhere to cell surfaces has been proposed as one important factor associated with the virulence of the organism (Matsuyama, 1977;Sat0 et al, 1979). This property has been examined by various methods including haemagglutination tests (Keogh and North, 1948), microscopic observations of bacteria attached to tissue-culture cells (Holt, 1972;Sat0 et al, 1981), microscopic and viable counts of bacteria bound to rabbit, hamster or chick tracheal organ cultures (Iida and Ajiki, 1974;Collier, Peterson and Baseman, 1977;Matsuyama, 1977) and the assessment of bacterial adhesion to mouse lungs by radiolabelling techniques (Burns and Freer, 1982). However, attempts to quantify these methods are prone to difficulties with enumeration, contamination or uneven distribution of surface cell types, which may interfere with accurate and reproducible measurements of bacterial adhesion.…”
mentioning
confidence: 99%